Trends in job demands among older workers, 1992-2002 - Johnson, Richard W. (Monthly Labor Review, 2004)
"The aging of the population raises concerns about the Nation's ability to support future retirees, whose numbers will soar once members of the 'baby-boom' cohort begin reaching old age in coming years. If current employment patterns persist, there will be fewer workers in the future available to produce goods and services, threatening standards of living for Americans of all ages. As long as job demands do not force many older workers into retirement, increasing employment among older adults could relieve these demographic pressures. This article explores the ability of the labor force to accommodate older adults by examining recent trends in job demands among older workers." (Monthly Labor Review)